Travel Planning Management System - Madushan S.H.K; De Alwis Gunathilake W.L.D.C.K; Jayasinghe J.A.S.C; D.V.P Ferdinando; D. I. De Silva; Piyumika Samarasekara (International Journal of Engineering and Management Research, 2022)
This project, "TRAVEL PLANNING MANAGEMENT SYSTEM", is used to automate all processes of travel and tourism, which deals with the creation, booking, confirmation, and user details. The project is designed with React JS as the front end and Spring boot as the backend, which works in any browser. A travel planning management system is used to book a tour from anywhere in the world by a single dynamic website which will help the user to know all about the places and travel details in a single web application. The admin can add travel packages to the system, transport services, place management, and hotels to create travel packages. Then the users can sign in and book each travel package, and also, they can book custom travel packages. The user can confirm their bookings by paying for the package. It is the most accessible platform for travellers who can easily book and know all details.